ANALISIS PENERIMAAN RETRIBUSI PASAR DI KOTA SEMARANG - Ardana Indra Permana; Herniwati Retno Handayani (Universitas Diponegoro, 2014)
ABSTRACTMarkets retribution is one of the potential user charge in the Semarang city. The increased income of market retribution from year to year has the potential to be developed. However, during the year 2008-2010 market retribution revenue were never able to meet the target.This study aims to analyze market retribution revenue in the Semarang city in the year 2002-2010. The independent variables used in this study is the total population, GDP percapita and the rate of inflation. This study used a secondary data per quarter from 2002-2010. Methods of data collection documentation methods, were analyzed using multiple linear regression analysis.The results showed that the variables of population and GDP percapita has a significant influence on the market retribution. Both of these variables have a positive relationship to market retribution. The population greatly affect the market retribution, the more people who visit the market will increase market acceptance of retribution GDP percapita have the positive relationship and significant to market acceptance of retribution. When GDP percapita is high then the ability of people to shop will be higher because of the need to shop can be met. The inflation rate has a negative and insignificant relationship with the market acceptance of retribution. F test results indicate that the variable overall population, GDP percapita and inflation rate together to show its affect on market acceptance of retribution. R2 value of 0,950, which menas a 95% market retribution receipts variation can be explained from the third variation of the independent variable while the rest is explained by other causes outside the model.